Gentlehands - Kerr, M. E. (New York : Harper & Row, 1978)
A teenage boy falls in love with an "upper-class" girl and gets to know his estranged grandfather in one heartbreaking summer which climaxes in a shattering search for Nazi war criminals.
"An Ursula Nordstrom book."
Keywords: Grandfathers -- Fiction; War criminals -- Germany -- Fiction